If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + -3h = 12 Solving -5 + -3h = 12 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3h = 12 + 5 Combine like terms: -5 + 5 = 0 0 + -3h = 12 + 5 -3h = 12 + 5 Combine like terms: 12 + 5 = 17 -3h = 17 Divide each side by '-3'. h = -5.666666667 Simplifying h = -5.666666667
| 13x+12-19x= | | x^3+6x^2+9x-3=0 | | 1000000+9+5000000+6= | | x+6x=46 | | 1000009+3009000= | | -5(x+3)=2x-15 | | 4-(5+x)=3 | | -3(x-2)+3x=-6 | | 1000000009+3009000= | | 2x-20-64=0 | | 4(2-3b)=62 | | 9u+4=19 | | y^2-y-132=0 | | g(x)=log(x-5) | | 8R-2=2R+6-4R | | 8x-(2x+6)=24 | | 9x^2+18y^4= | | 66*8= | | 32b^2+12b= | | 3u+(u-2)=10 | | y^2-10y=-23 | | (x-2)5=0 | | (x-2)5=x | | 6a^3+15a= | | 5x+3y=-8 | | 5r^2-26r=24 | | 4b^2-17b=15 | | 18.3x-7.6=8.4x-14.6 | | 3t^2-13t-16=0 | | (2x+1)(x-4)(3x+5)=0 | | 5x-2(x-2)=11 | | -8x+20+10x=42 |